Application of major histocompatibility complex in laboratory chickens - Gao-Xia, G.; Lingxia Han; Han Jianlin (2010)
Chicken major histocompatibility complex (MHC) has been a research focus for its high polymorphism and close relation with varying resistance against diseases. It is located on a microchromosome (chromosome 16). It has been found that it has different resistance against diseases for different B haplotypes. The article gives a detailed introduction about structural characteristics, relation to diseases resistance, the progress in detection methods of chicken MHC, and the prospect of application of MHC in molecular breeding for disease resistance in chickens.